Penerapan Unsur Kesengajaan Pasal 2 UU TPPO Terhadap Perekrut Sebagai Dasar Pertanggunjawaban Pidana - Retnowati Boong, Vicariya; Mugiono, Mariana (Journal of Contemporary Law Studies, 2025)
This study aims to analyze the application of the element of intent under Article 2 of Law Number 21 of 2007 concerning the Eradication of the Crime of Trafficking in Person, specifically as it relates to recruiters and their criminal liability. The focus is on determining whether a recruiter can be held liable when they claim to act solely as an intermediary without explicit knowledge of exploitation. This study employs a normative juridical method, employing both statutory and conceptual approaches. Legal norms and principles relevant to the concept of intent in criminal law are examined, along with an analysis of applicable laws and doctrinal interpretations in the context of human trafficking cases. The findings of this study reveal that intent under Article 2 of the Law on Trafficking in Persons encompasses both direct and indirect forms. Direct intent refers to situations where the perpetrator explicitly knows and aims to carry out exploitation. In conclusion, Article 2 of the Law on Trafficking in Persons is not limited to demonstrable knowledge of exploitation. It can also encompass situations where the recruiter should have had reasonable suspicion of potential exploitation but ignored warning signs. Therefore, recruiters can be held criminally liable as principal perpetrators when it is proven that their actions contributed to the trafficking chain, and they knew or should have known of the risks of exploitation involved.